Application of the group-contribution lattice-fluid equation of state to random copolymer-solvent systems - Lee, BC; Danner, RP (ELSEVIER SCIENCE BV, 1996)
A group-contribution lattice-fluid equation of state (GCLF-EOS), which is capable of predicting the equilibrium properties of polymer-solvent solutions, has been developed. Group contributions for the interaction energy and reference volume have been developed, based only on the saturated vapor pressures and liquid densities of low molecular weight compounds. For a mixture, group contributions of the binary parameter have been developed from the binary vapor-liquid equilibria of low molecular weight compounds. The model can be applied to the prediction of activity coefficients of solvents in random copolymers. The only input required for the model is the structure of the molecules in terms of their functional groups. No other pure component or mixture properties of the polymer or solvent are needed.
Keywords: POLYMER-SOLUTIONS; MIXTURES